Transforming Modes of Production and Class Dynamics in Nepal: An Anthropological Perspective - Pokharel, Binod (State, Society and Development: PMPD Perspectives, 2025)
This paper briefly highlights the nature and causes of social and economic changes in Nepal. It aims to explain and analyze Nepali society from a political-economic perspective, drawing on the concept of People’s Multiparty Democracy (PMPD) as propounded by Madan Bhandari. The analysis is based on a review of existing literature. Although Nepal’s economic and political system is theoretically socialist-oriented and practically market-based, it is marked by crony capitalism and comprador practices rooted in specific social relations. The paper argues that Nepal’s current politico-economic structure broadly resembles financial capitalism, where money begets more money. From a Marxist perspective—which views all activities, including habits, behaviors, and even addictions, as shaped by the economic system—it is evident that customs and cultures are deeply influenced by financial capitalism. The internal and external conditions in Nepal do not align with socialist ideals. Hence, socialism must be redefined in line with Nepal’s specific context, as envisioned by Bhandari in his theory of people’s multiparty democracy. The development of a self-reliant agricultural system, food sovereignty, increased production, equitable distribution, and universal access to health and education has laid the groundwork for socialism. This paper concludes that both Eurocentric Marxist and non-Marxist frameworks fall short in explaining Nepal’s transformation. In light of global historical and political shifts, traditional Marxist theory alone is inadequate for understanding Nepal’s situation. Bhandari’s vision of people’s multiparty democracy provides a valuable lens for analyzing Nepali society on its own terms.